Micro Roles and the Information-Seeking Behaviour of Seniors - Wicks, Don A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
It is well known that in Canada and many other countries population statistics reveal an aging population, with many more people moving into the senior age category as "baby boomers" reach retirement over the next decade. For many years this trend has been noted in the library literature (e.e. Nauratil, 1995; Moore & Young, 1985). Currently, Statistics Canada (1998) reports that there are. . .